Government transfers in the budgets of Polish municipalities and their determinants - Wichowska, Anna (Rozwój Regionalny i Polityka Regionalna, 2022)
The level of transfer payments, factors that determine the allocation of public resources to territorial governments, and fiscal decentralization have been studied extensively for many decades. These problems have recently resurfaced in the scientific debate in the face of the economic crisis triggered by the coronavirus pandemic. The study has two aims: to evaluate the vertical redistribution of public funds to Polish municipalities, and to identify the economic factors that influence the level of transfer payments. The poverty rate and the average monthly disposal income in Polish municipalities were among the key determinants of public transfer levels.